Suggested role-play activities to develop cognitive skills among disadvantaged preschool fast learners - Nava, Lucina Laroya 1946- (College of Education, University of the Philippines Diliman, 1977)
Role-play, an activity in which the child undertakes a make believe role and expresses it in imitative action and/or verbalization, has been found in a number of studies to be an effective tool in developing cognitive skills among disadvantaged learners. The fifteen suggested role-play activities were tried out with 18 disadvantaged preschool fast learners for one and a half months. From the try-out, it could be deduced that role-play activities can help develop cognitive skills such as labeling, identifying, classifying, discriminating and categorizing which are very essential to conceptualization. Concommitantly, role-play technique also develops the affect as youngsters empathize with the different characters in the role-play situation.